AC withstand voltage of palm oil based CuO nanofluids with CTAB, SDS and OA - Mohamad, Nur Aqilah; Azis, Norhafiz; Haron, Ahmad Razani; Thien, Yee Von; Yaakub, Zaini (IEEE, 2022)
The intent of this research paper is to examine the AC withstand voltage of palm oil based CuO nanofluids while considering varieties of surfactants. Refined, Bleached and Deodorized Palm Oil (RBDPO) was used in this investigation, whereas mineral oil was used as a reference. This experimental work used Cetyl Trimethyl Ammonium Bromide (CTAB), Sodium Dodecyl Sulfate (SDS) and Oleic Acid (OA) as surfactants. The ratio of the volume concentration surfactant to the nanoparticles was fixed to 1:2. The AC breakdown voltage tests for RBDPO and mineral oil were conducted at gap distance of 1 mm according to ASTM D1816 of which the AC withstand voltage at 1% probability was obtained using Weibull distribution. It is found that the AC withstand voltage at 1% probability is much greater for RBDPO-based CuO with various surfactants than that mineral oil.